1981
DOI: 10.1086/130828
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic study of the binary Be star Phi Persei

Abstract: High-dispersion high signal-to-noise ratio spectrograms of 4> Per have been obtained. The radial velocities of various spectral features have been measured and an orbit solution obtained. The (j> Persei system is found to consist of a 21 W© star, whose Vsin i is 450 km s -1 , and a 3.4 S .W© secondary. The secondary is peculiar in that Hell À4686 emission arises from within its vicinity. It is suggested that the secondary is the helium core of a once more massive star, its mass having been transferred to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 4 publications
2
48
1
Order By: Relevance
“…More detailed work followed this period, and Slettebak (1966) (confirmed later on by Abt et al 2002) published a measurement of the projected rotational velocity of V sin i = 410-450 km s −1 , which is estimated to be around 85% of the equatorial breakup velocity. Poeckert (1981) presented the first evidence of a companion in ϕ Persei and identified it as a helium star. Based on the velocity curves, he estimated masses of M p = 21 M and M s = 3.4 M .…”
Section: Main Characteristics Of ϕ Perseimentioning
confidence: 99%
See 2 more Smart Citations
“…More detailed work followed this period, and Slettebak (1966) (confirmed later on by Abt et al 2002) published a measurement of the projected rotational velocity of V sin i = 410-450 km s −1 , which is estimated to be around 85% of the equatorial breakup velocity. Poeckert (1981) presented the first evidence of a companion in ϕ Persei and identified it as a helium star. Based on the velocity curves, he estimated masses of M p = 21 M and M s = 3.4 M .…”
Section: Main Characteristics Of ϕ Perseimentioning
confidence: 99%
“…There are several features in the optical spectrum that display the antiphase Doppler shifts expected for the companion, but these are usually associated with gas near the companion star. These include weak He II 4686 Å emission that may form in a disk close to the companion (Poeckert 1981), He I 4026 Å, 4471 Å "shell" lines formed farther away (Poeckert 1981), and the He I 6678 Å emission line that probably originates in the outer disk of the Be star facing the hot subdwarf (Štefl et al 2000;Hummel & Štefl 2001). There are only six HST measurements of the photospheric lines of the companion itself that were made in the far-ultraviolet spectrum by Gies et al (1998), and we include these in Table 2.…”
Section: Spectroscopic Orbital Determination From Radial Velocity Meamentioning
confidence: 99%
See 1 more Smart Citation
“…Already Plavec (1976) pointed out that if all Be stars were binaries with Roche-lobe filling secondaries, one should observe more eclipsing binaries among them than what is actually observed. While Harmanec (1987) slightly weakened this objection, there is a stronger one: detailed studies of several known Be binaries (ϕ Per = HD 10516: Poeckert 1981, Gies et al 1998; V839 Her = 4 Her: Koubský et al 1997, for instance) clearly demonstrated that the secondaries in those binaries are not Roche-lobe filling objects but very small stars. The same is also true of binaries composed of a Be star and a compact, X-ray companion.…”
Section: Attempts To Explain the Be Phenomenonmentioning
confidence: 99%
“…No confirmed examples of the Be + He star stage were known until recent FUV spectroscopy with the Hubble Space Telescope led to the discovery of a hot subdwarf orbiting <f> Per, one of the brightest Be stars in the sky, and in the next section I describe the observations of this remarkable binary. Poeckert (1981) made the first definitive orbital solution for the Be star, <f> Per (P = 127 d). Poeckert noted the unusual appearance of He II A4686 emission with an anti-phase velocity curve, and he argued that the companion must be a hot object in order to ionize helium.…”
Section: Giesmentioning
confidence: 99%